Polanyian Reading of the Socio-Economic Transformation of the European Union - Savevska, Maja (Journal of Contemporary European Studies, 2014)
In an attempt to analyse the socio-economic transformations of the European Union, an increasing number of scholars have resorted to Polanyi's double movement thesis. In doing so, some scholars, by looking at the evidence of intensified marketisation of social relations, consider the EU disembedded; whereas others identify a re-embedding tendency in the recent surge of socio-environmental protection. The paper follows Lacher, Burawoy, Dale and Streeck's readings of Polanyi and argues that the exiting socio-environmental provisions do not re-embed the economy. Socio-environmental protection does not eclipse the neoliberal accumulation strategy which continues to propagate the disembedding tendency, because it fails to decommodify fictitious commodities. The EU is characterised by a heightened intensification of both disembedding and protective tendencies, which Polanyi contends is disruptive in nature. What emerges out of the dialectics between neoliberalisation and socio-environmental provisions is a decelerated rate of change, which, although it temporarily secures the habitation of man, prevents the inception of a synthesis that is capable of sublating the contradictions of the marketisation/protection binary. Moreover, we have a paradoxical situation wherein the socio-environmental measures, despite their protective invocation, are predicated on deepened commodification.
Keywords: Polanyi; disembedded; commodification; European Union; double-movement